Personality as correlate of perceived job stress among electoral officers during elections (2004)
This study examined the relationship of personality (conscientiousness dimension) with electoral officers perceived job stress during election. The survey utilised the expost facto research design. A total of 346 participants responded to the questionnaires. In all, 254 (70.4%) were males and 101 (29.6%) were females. Their age ranged between 25 to 50 years with a mean age of 38. 7 (SD = 7.38). Structured questionnaires were employed for data collection and the hypothesis was tested using Pearson moment product correlation, Results showed that conscientiousness had significant positive relationship with job stress; which is an indication that personality quality play important role in electoral officers stress during elections (r = 0,71, P < 0,01). Based on the findings, recommendation was made